Combining root architecture, root function and soil management to improve production efficiency and quality of apples - Cobo-Medina, Magdalena (2024)
Rootstock-induced dwarfing is a complex mechanism that causes a reduction in the size of the grafted scion by altering the floral and vegetative balance. Dwarfing rootstocks are essential to intensive production methods since they crop more and earlier. The impact of rootstock-induced dwarfing has previously been widely studied in scions but little is known about the role of dwarfing on root architecture. With the increase in food demand and climate change, it is essential to understand the impact of dwarfing on root architecture and how rootstocks can be optimised for both productivity and resilience to better adapt to future climate conditions.